2018
DOI: 10.20473/mog.v25i12017.6-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor of severe preeclampsia in Dr. Soetomo Hospital Surabaya in 2015

Abstract: Objectives: to determine which of the risk factors above associated with the occurrence of severe preeclampsia at dr. Soetomo Hospital, Surabaya during 2015.Materials and Methods: The type and design of the study were analytic and retrospective. This study was held in the dr. Soetomo Hospital from April until November 2016. The instrument of the study was the medical records then being coded and analysed. The samples were 134 pregnant women, consisting of 67 pregnant women with severe preeclampsia as cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
(2 reference statements)
1
5
0
2
Order By: Relevance
“…Pregnant women with obese BMI have a 5.8 times higher risk factor for severe preeclampsia compared to pregnant women with normoweight BMI. 24 These results are in accordance with previous literature which states that obesity is a risk factor for severe preeclampsia. In obese mothers, severe preeclampsia can occur through the mechanism of hyperleptemia, metabolic syndrome, inflammatory reactions and increased oxidative stress that causes endothelial damage and dysfunction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Pregnant women with obese BMI have a 5.8 times higher risk factor for severe preeclampsia compared to pregnant women with normoweight BMI. 24 These results are in accordance with previous literature which states that obesity is a risk factor for severe preeclampsia. In obese mothers, severe preeclampsia can occur through the mechanism of hyperleptemia, metabolic syndrome, inflammatory reactions and increased oxidative stress that causes endothelial damage and dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with the research of Kartika et al that the result of parity analysis was p = 0.854, which means that there is no significant relationship between parity and the incidence of severe preeclampsia, with OR = 1.145 (95% CI: 0.556-2.356) which means that parity is not a risk factor. 24 In contrast to retrospective cohort studies conducted by Das et al In 2019 regarding the incidence and risk factors for preeclampsia in Nepal, it was stated that primiparous pregnant women had a 2 times greater risk of experiencing severe preeclampsia than multiparous pregnant women. This is associated with the first exposure to chorionic villi (of fetal origin) and associated maternal immunologic incompetence is more likely to occur during the first pregnancy and may increase the risk of developing preeclampsia.110 Different results were shown in the study of Denantika et al in 2015 where multigravida (53.1%) suffered more from preeclampsia than primigravida (46.9%).115 Research by Sahay et al in 2015 it was found that more than half of the subjects in the preterm preeclampsia group were multipara, and more than half of the subjects in the term preeclampsia group were nullipara.116 This is different from the study of El Shahat et al In 2013, multigravida was more commonly found in normal pregnancies (72.2%) than preeclampsia (58.3%).…”
Section: Discussionmentioning
confidence: 92%
“…Incidence of pre-eclampsia in developing countries is approximately seven times higher than in developed countries (on average 2.8% of live births versus 0.4%) [5,6]. Nepal is a developing country and pre-eclampsia/eclampsia is second leading cause of maternal morbidity and mortality in Nepal [7].…”
Section: Introductionmentioning
confidence: 99%
“…Preeclampsia is one of the leading causes of maternal death, which results in estimated 50,000-60,000 deaths every year worldwide. The incidence of preeclampsia in developing countries is about seven times higher than in developed countries (average 2.8% of live births vs. 0.4%) [4], [5]. Maternal mortality due to preeclampsia is increasing every year in Indonesia.…”
Section: Introductionmentioning
confidence: 98%